2007
DOI: 10.1631/jzus.2007.b0885
|View full text |Cite
|
Sign up to set email alerts
|

A case of chylothorax treated curatively with Sapylin, a streptococcus preparation

Abstract: Abstract:Chylothorax is an uncommon disease where fatty fluid accumulates within the chest cavity. Conservative management, including repeated thoracentesis or pleurodesis, seems to be suitable to most cases. Herein, we present a case of efficacious pleurodesis by intrapleural injection of Sapylin, a streptococcus preparation, for the treatment of chylothorax. A 52-year-old non-smoking female farmer was diagnosed as idiopathic chylothorax after we ruled out possible causes including chest trauma, lymphoma, lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The aluminosilicate increases the melting point of the ash and reduces the corrosion of the surface of the metal sample [16]. Calcium oxide and calcium carbonate in dolomite and limestone do not directly participate in the reaction, but can dilute the ash, thereby inhibiting the melting and agglomeration of ash [17].…”
Section: Effect Of Additives On Ash Corrosion 12crmovgmentioning
confidence: 99%
“…The aluminosilicate increases the melting point of the ash and reduces the corrosion of the surface of the metal sample [16]. Calcium oxide and calcium carbonate in dolomite and limestone do not directly participate in the reaction, but can dilute the ash, thereby inhibiting the melting and agglomeration of ash [17].…”
Section: Effect Of Additives On Ash Corrosion 12crmovgmentioning
confidence: 99%
“…As the policy maker, the government had a variety of contradictions and dissensions with forest farmers, such as the complex transfer procedures, the ambiguous definition of the right and the rising fees and taxes. To promote forestland transfer, the government must set up the trading centers and intermediary service organizations and strengthen the supervision and management [26]. In addition, Xie and Wen found that the higher proportion of non-agricultural income was, the less probability of forestland and timber transfer was [27].…”
mentioning
confidence: 99%